2008
DOI: 10.1016/j.str.2007.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Activation and Inhibition of the HER4/ErbB4 Kinase

Abstract: HER4/ErbB4 is a ubiquitously expressed member of the EGF/ErbB family of receptor tyrosine kinases that is essential for normal development of the heart, nervous system, and mammary gland. We report here crystal structures of the ErbB4 kinase domain in active and lapatinib-inhibited forms. Active ErbB4 kinase adopts an asymmetric dimer conformation essentially identical to that observed to be important for activation of the EGF receptor/ErbB1 kinase. Mutagenesis studies of intact ErbB4 in Ba/F3 cells confirm th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
163
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(172 citation statements)
references
References 44 publications
9
163
0
Order By: Relevance
“…2A, a solution of 1 μM mant-ATP (plus 5 mM MgCl 2 ) shows little fluorescence when excited at 280 nm, but a significant peak centered at 448 nm appears when 3 μM ErbB-TKD is added. This peak reflects FRET from tryptophans and/or tyrosines in the protein to the bound mant-ATP and is seen only when ErbB3-TKD, MgCl 2 , and mant-ATP are all present in the sample ( (27). Consistent with its reduced autophosphorylation activity (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…2A, a solution of 1 μM mant-ATP (plus 5 mM MgCl 2 ) shows little fluorescence when excited at 280 nm, but a significant peak centered at 448 nm appears when 3 μM ErbB-TKD is added. This peak reflects FRET from tryptophans and/or tyrosines in the protein to the bound mant-ATP and is seen only when ErbB3-TKD, MgCl 2 , and mant-ATP are all present in the sample ( (27). Consistent with its reduced autophosphorylation activity (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…3A, the overall structure of ErbB3-TKD 665-1001 closely resembles inactive conformations of the EGFR, ErbB4, and Src kinases (5,27). Helix αC of ErbB3-TKD 665-1001 is displaced from the active site, in the "out" position typically seen in structures of inactive kinases (28).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Remarkably, we found that the inactive HER4 kinase domain also forms a very similar N-lobe dimer [Protein Data Bank (PDB) ID codes 3BBT and 3BBW], although it crystallizes with different lattice symmetry (space group P6 1 for HER4 compared with C2 for the HER3 crystals) (Fig. 4 A and B) (27).…”
Section: Resultsmentioning
confidence: 99%
“…Compelling evidence has revealed that, in contrast with most receptor-tyrosine kinases, phosphorylation of the activation loop is not required for activation of ERBB kinases (9,38). Structural studies have provided evidence that EGFR (39) and ERBB4 (40) kinases are activated through an allosteric mechanism via formation of an asymmetric dimer. Upon dimer formation, the helix ␣C of one kinase domain is restrained to the catalytically competent conformation by the C-lobe of the other.…”
Section: Discussionmentioning
confidence: 99%